INTENSITY OF KOREAN DRAMA PROGRAM IN TELEVISION- INTERACTIONS OF PEER GROUP, AND ITS INFLUENCE TOWARD K-STYLE IMITATION BEHAVIOUR AMONG TEENAGERS - Dita Kusumasari (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2017)
Fashion is a part of people's lifestyle, especially teenagers. Their needs in seeking for an identity and being recognized make them pay more attentions to every thing that are booming in their circles. Local trend can be spread quickly to the entire world because of the improvement of mass media’s effect. Through Korean drama, people of Indonesia got enough details about Korean fashion, called K-Style. K-Style surprisingly attracted the teen audience and motivated them to imitate those styles. Peer Group Interactions also take an important role in K-Style imitation behavior. Necessities for being praised and accepted made their personality became capricious and emotionally unstable. For that reason, this study aims to analyze the influence of intensity of Korean drama program in television and Peer Group Interactions to K-Style imitation behavior among teenagers.